The Potential Role of Aerobic Exercise-Induced Pentraxin 3 on Obesity-Related Inflammation and Metabolic Dysregulation. (19th March 2017) - Slusher, Aaron L.; Huang, Chun-Jung; Acevedo, Edmund O.
Abstract : Obesity is defined as the excess accumulation of intra-abdominal body fat, resulting in a state of chronic, low-grade proinflammation that can directly contribute to the development of insulin resistance. Pentraxin 3 (PTX3) is an acute-phase protein that is expressed by a variety of tissue and cell sources and provides an anti-inflammatory property to downregulate the production of proinflammatory cytokines, in particular interleukin-1 beta and tumor necrosis factor alpha. Although PTX3 may therapeutically aid in altering the proinflammatory milieu in obese individuals, and despite elevated expression of PTX3 mRNA observed in adipose tissue, the circulating level of PTX3 is reduced with obesity. Interestingly, aerobic activity has been demonstrated to elevate PTX3 levels. Therefore, the purpose of this review is to discuss the therapeutic potential of PTX3 to positively regulate obesity-related inflammation and discuss the proposition for utilizing aerobic exercise as a nonpharmacological anti-inflammatory treatment strategy to enhance circulating PTX3 concentrations in obese individuals.